MiRNAs: a new target for Chinese medicine to repair the intestinal barrier in the treatment of ulcerative colitis - Sun, Dajuan; Zhang, Zhongtao; Xue, Jingwei (Frontiers in Pharmacology, 2024)
Ulcerative colitis (UC) is a chronic nonspecific inflammatory bowel disease whose pathogenesis remains unclear. Dysfunction of the intestinal mucosal barrier is closely related to the pathogenesis of UC, which is characterised by damage to the colon epithelial barrier, disruption of immune homeostasis, and persistent inflammatory cell infiltration. MicroRNAs (miRNAs) exhibit specific or differential expression in both UC animal models and patients , implicating their involvement in the pathogenesis of UC. In recent years there has been progress in using Traditional Chinese medicine (TCM) to regulate miRNA expression for repairing the intestinal mucosal barrier in UC, as demonstrated in animal and cell experiments. However, it has not been applied in a clinical setting and its underlying molecular mechanisms require further investigation. Therefore, this study systematically described the role of miRNAs in UC-induced intestinal barrier damage and the application of TCM to repair this intestinal barrier by regulating miRNA expression, offering new therapeutic targets for UC treatment.